INTEGRATING WEST KALIMANTAN FOLKLORE INTO CHILDREN’S LITERATURE COURSE: A CREATIVE WRITING PROJECT - Sistiadinita; Ahmad, Ahmad; Zahroh, Adiba Qonita; Ramadhani, Rezky (Direktorat Riset dan Pengabdian kepada Masyarakat, Universitas Bina Darma, 2025)
This study explores how West Kalimantan folklore can be integrated into a children's literature class at STBA Pontianak through a creative writing project. The aims are to encourage students to understand local culture through storytelling and identify the elements of folklore. The analysis is based on three selected stories: The Curse of Jubata (Kapuas Hulu), The Adventure in Lawang Kuari Cave (Sekadau), and The Adventure of Bujang Beji (Sintang). The study uses Alan Dundes’ theory (2007) to examine students’ writing using four folkloristic elements: Tradition, Cultural Transmission, Variation, and Group Consciousness. The findings show that the stories reflect continuity of local beliefs, moral values, and harmony among communities, predominantly Dayak and Malay, as appeared in the chosen stories. The study suggests that Dundes’s framework can serve as a practical tool for developing creative writing rubrics in a multicultural classroom. By linking folkloristic theory with pedagogy, teachers can help students appreciate their cultural heritage while strengthening critical and creative skills. Future research should validate this rubric and explore broader applications of folklore-based learning across different cultural settings.